1976
DOI: 10.1111/j.1600-0560.1976.tb00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Giant and “Granular Melanosomes” in Leopard Syndrome: An Ultrastructural Study

Abstract: Electron microscopy of lentigines was performed to study the pigmentation abnormality in two children with LEOPARD syndrome. Giant melanosomes similar to those seen in café-au-lait spots of neurofibromatosis and nevus spilus were found in a lentigine from one of our cases. Our results show that "spherical granular melanosomes" described in neurofibromatosis, are lysosomal-like structures associated with the development of complex melanin granules. Our study also demonstrates that immature melanosomes are prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 9 publications
1
24
1
Order By: Relevance
“…These authors suggested that the distribution pattern of melanosomes was dependent upon the size of melanosomes irrespective of race. The presence of individual melanosomes smaller than 0.8 mm in kératinocytes in the present investigation and in the kératinocytes of the lentigines in LEOPARD syndrome [3] suggests that the distribution of melanosomes is not necessarily dependent on race or size. Our findings are further supported by the obser vations of Takahashi [17], who found singly dispersed melanosomes in kératinocytes of nevus spilus but melanosomal complexes in café au lait spots, even though there was no difference in the size of melanosomes.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…These authors suggested that the distribution pattern of melanosomes was dependent upon the size of melanosomes irrespective of race. The presence of individual melanosomes smaller than 0.8 mm in kératinocytes in the present investigation and in the kératinocytes of the lentigines in LEOPARD syndrome [3] suggests that the distribution of melanosomes is not necessarily dependent on race or size. Our findings are further supported by the obser vations of Takahashi [17], who found singly dispersed melanosomes in kératinocytes of nevus spilus but melanosomal complexes in café au lait spots, even though there was no difference in the size of melanosomes.…”
Section: Discussionmentioning
confidence: 62%
“…It is possible that melanosomes are transferred into kératinocytes at a speed much greater than their ability to aggregate them in complexes in the hypermelanotic state of Becker's melanosis as seen here, lentigines of LEO PARD syndrome [3] and nevus spilus [17]. Takahashi [17] supposed that melanosomal complexes in café au lait spots were seen because melanosomes were produced more abundantly.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The melanization of the giant melanosomes is usually most pronounced at its centre. The significance of this alteration in melanosomal morphology is as yet unclear [22], Giant melanosomes occur frequently in naevus spilus [21] and in café au lait spots of neurofibromatosis [15], rarely in lentigines [1], naevus cell naevi and in normal skin [23]. When present, they can be easily detected by light microscopy ( fig.…”
Section: The Subccllular Unit Of Melanin Synthesismentioning
confidence: 99%